ANTIOXIDANT PRODUCTION FROM LOCAL FUNGAL ISOLATE - & Al – Shamary, Ahmed (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2019)
This study aim was  antioxidant production from local fungal isolate, Twenty six purified isolates of Aspergillus sp. were obtained by using different sources ( soil, Spoiled fruits, wheat, barley, maize and Spoiled bread). The isolates were examined for their aflatoxins production, Non-aflatoxins producing isolates were used as phenolic compounds producer. The highest phenolic compounds (45.3 µg/ml) was obtained from  Aspergillus sp.BP1 isolate. This isolate was identified by 5.8 rRNA gene sequecing as Aspergills niger (accuracy of 100%), which was matched with the sequence of Aspergills niger strain YMCHA 55 recorded in Gene bank under the ID: JF 436883.1.The Phenolic compounds were extracted from filtrate of selected isolate by ethyl acetate and identified using high performance liquid chromatography analysis (HPLC) and the results were compared with  that for standard phenolic compounds, It was found that the filtrate extract contains gallic acid, cumarin, rutin and kampferole with concentrations of 47.69,  6.60, 218.30 and 22.00 µg/ml respectively.